1985
DOI: 10.7567/jjaps.24s2.640
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance of 51V in BiVO4 Single Crystals

Abstract: Nuclear magnetic resonance spectra of 51V (I=7/2) in ferroelastic BiVO4 single crystals grown by the Czochralski method have been investigated by employing a wide-line Varian spectrometer. The seven line structure due to the quadrupole interaction was measured at a fixed frequency of 15 MHz in three mutually perpendicular crystal planes at room temperature and 77 K, well below its ferroelastic Curie temperature of 523 K. From the experimental data the quadrupole coupling constant, e 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…3 Euler angles between principal axis systems of the two interactions (0^16¡, 66^9¡, 169^14¡) were determined and satisfy the crystallographic symmetries. However, this orientation is only consistent with the results of Choh et al 4 if the b angle is regarded as 90¡.…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…3 Euler angles between principal axis systems of the two interactions (0^16¡, 66^9¡, 169^14¡) were determined and satisfy the crystallographic symmetries. However, this orientation is only consistent with the results of Choh et al 4 if the b angle is regarded as 90¡.…”
Section: Resultscontrasting
confidence: 41%
“…The lineshape is mainly governed by the CSA, whose parameters can thus be extracted with good reliability. The measured span of the CSA is slightly greater than the result reported by Lapina et al 3 The reÐnement exe- (6,8,4) cuted with the previously reported quadrupolar parameters (s \ 4.8 MHz and gives the same result g Q \ 0.38) for the CSA parameters. Even when the quadrupolar interaction is set to zero, the CSA parameters remain unchanged.…”
Section: Determination Of Chemical Shift Anisotropysupporting
confidence: 46%
“…Recently, a number of experiments, e.g. X-ray and neutron diffraction [5], Raman scattering [6][7][8], NMR [9][10][11][12], and EPR [13][14][15][16] have been carried out to investigate structural changes, phase transitions, and optical properties of BiVO4. EPR is a powerful technique in studies of local site symmetry around paramagnetic impurities in crystals.…”
Section: Introductionmentioning
confidence: 99%